The Impact of Pavlov on the Psychology of Learning in English-Speaking Countries - Boakes, Robert A (The Spanish Journal of Psychology, 2003)
The translation of Pavlov’s lectures (Pavlov, 1927) provided English-speaking psychologists with access to the full scope of Pavlov’s research and theoretical ideas. The impact this had on their study of the psychology of learning can be assessed by examining influential books in this area. This reveals that Watson (1924) had been highly effective in promoting the misleading idea that Pavlov was a fellow S-R theorist. This assumption was not questioned by Tolman (1932), Hilgard and Marquis (1940) or by Hull (1943). However, this mistake was not made by Skinner (1938), who also provided the strongest arguments against Pavlov’s belief that behavioral effects required explanation in terms of physiological processes. Post-1927 most learning research in the English-speaking countries continued to use instrumental, rather than Pavlovian, conditioning procedures. Nevertheless, many of the issues addressed by this research were ones that Pavlov had been the first to raise, so that his major influence can be seen as that of defining a research program for subsequent students of learning.